(untitled) (Revista Cocar, 2019)
Arlindo Clemente: expert in education and its contibuition for the writing of the History of Mathematical Education Resumo: O presente trabalho é um recorte de uma pesquisa de doutorado em andamento que trata do ensino de Matemática nas escolas industriais brasileiras. Em particular, este artigo trata a respeito da atuação do professor e engenheiro Arlindo Clemente, docente da antiga Escola Técnica Nacional (ETN), atualmente CEFET/RJ. Com base nas discussões teóricas de Hofstetter, Schneuwly e Freymond (2017) a respeito do termo “expert”, o texto se dispõe a caracterizar o professor como um expert e verificar quais saberes foram produzidos e divulgados. Como conclusão verifica-se que Arlindo Clemente é um expert em educação, pois recebeu a missão de produzir saberes e de fazê-los circular e o fez com reconhecimento. Palavras-Chave: Expert. Ensino Industrial. Matemática. Abstract: The present work is a cut of an ongoing doctoral research that deals with the teaching of Mathematics in Brazilian industrial schools. In particular, this article deals with the work of the teacher and engineer Arlindo Clemente, a professor at the former National Technical School (ETN), currently CEFET / RJ. Based on the theoretical discussions of Hofstetter, Schneuwly and Freymond (2017) regarding the term "expert", the text sets out to characterize the teacher as an expert and to verify which knowledge has been produced and disseminated. As a conclusion, it is clear that Arlindo Clemente is an expert in education, since he was given the mission of producing knowledge and of making them circulate and did so with recognition. Keywords: Expert. Industrial Education. Mathematics.